Indonesia’s Strategic Narrative on the New Dynamics of Great Power Rivalry in the Indo-Pacific - Budi Riyanto; Darmansjah Djumala; Youzhi Tan (JAS (Journal of ASEAN Studies), 2023)
Given the rising political tensions between the two great powers, the United States (U.S.) and the People's Republic of China (PRC), a geopolitical shift to the Indo-Pacific region is critical momment in the 21st century. Ideological, economic, military and technological aspects of this new struggle appear to be sharpening. In the current geopolitical change in the Indo-Pacific, two concerns that have not received much attention are addressed in the research, namely the importance of strategic narrative competition in the global information era and the part played by Indonesia in terms of its strategic narratives as a nation in the center of Indo-Pacific geopolitics. By focusing on the interaction of each actor in projecting a story about the order in the new world system, encouraging actors to adapt to their identities and roles in the story, and enacting policies that are in line with their interests, strategic narrative studies have the potential to explore geopolitical issues more thoroughly. Indonesia positions itself actively in a strategic narrative construction that can compete, and create a strategic role that can be played in accordance with its interests rather than playing a passive role and only becoming a victim in the face of the strategic narrative contestation among the great powers. The strategic narrative of Indonesia as it relates to identity, policy, and system is specifically examined in the research. It also examines the role that Indonesia plays in the formulation and projection of the narratives, as well as how the narratives are received in the context of the emerging Indo-Pacific's geopolitical struggle. As a middle power, Indonesia offers a shared strategic narrative that promotes a goal of greater cooperation, hence reducing great power rivalry.